2007
DOI: 10.1590/s1806-83242007000400011
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antimicrobial efficiency of a mouthwash containing triclosan/gantrez and sodium bicarbonate

Abstract: Several antiseptic substances have been used as adjuncts to routine mechanical procedures of oral hygiene, based on their antimicrobial effects. The objective of this study was to assess in vitro the antimicrobial efficiency of a mouthwash containing Triclosan/Gantrez and sodium bicarbonate in comparison to both positive and negative controls. Standard strain samples of Escherichia coli, Pseudomonas aeruginosa, Actinomyces viscosus and Bacillus subtilis were used. Samples of Streptococcus mutans and Gram-negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 8 publications
(9 reference statements)
1
22
0
2
Order By: Relevance
“…Pires et al (Pires, et al, 2007) have concluded that a mouthwash containing a combination of Triclosan/Gatrez and sodium bicarbonate has an in-vitro antimicrobial activity superior to that of a placebo, but still inferior to that of chlorhexidine.…”
Section: Other Antimicrobial Mouthrinsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pires et al (Pires, et al, 2007) have concluded that a mouthwash containing a combination of Triclosan/Gatrez and sodium bicarbonate has an in-vitro antimicrobial activity superior to that of a placebo, but still inferior to that of chlorhexidine.…”
Section: Other Antimicrobial Mouthrinsesmentioning
confidence: 99%
“…In vitro studies show antimicrobial activity superior to that of a placebo, but inferior to that of chlorhexidine (Pires, et al, 2007) Siegrist et al (Siegrist, et al, 1986) Listerine Peridex Placebo Double blind, controlled clinical trial. After a baseline complete dental prophylaxis,124 healthy adults used the mouthrinse as a supplement to regular oral hygiene for 6 months.…”
Section: Triclosan Not Available In the Us N/a Triclosanmentioning
confidence: 99%
“…It is usually combined with either zinc citrate or a copolymer of methoxyethylene and maleic acid, in which form it is effective in reducing plaque and gingivitis (Ciancio, 1987). A non-ionic phenol derivative, Triclosan has a broad spectrum antimicrobial activity against gram positive and gram negative bacteria and has been shown to be beneficial in toothpaste (Pires et al, 2007). Triclosan acts on the microbial cytoplasmic membrane to induce leakage of cellular constituents and bacteriolysis (Rolla et al, 1996).…”
Section: Toothpastesmentioning
confidence: 99%
“…23 However, besides being antibacterial in nature, chlorhexidine also has local side effects when used as a mouthwash that is it can cause extrinsic staining on the teeth so that the teeth become dark yellow brown. 21 Based on these research, it can be concluded that the essential oil of lemon peel (Citrus aurantifolia swingle) of concentration 1%, 2%, 3% and 4% can reduce the production of CH 3 SH (methyl mercaptan) compound on halitosis-causing bacteria, Porphyromonas gingivalis. …”
mentioning
confidence: 97%
“…Chlorhexidine is an antibacterial active ingredient belonging to the gold standard contained in mouthwash. 21 Chlorhexidine has a broad-spectrum antibacterial activity both against the Gram positive and Gram negative. 22 Antimicrobial activities of chlorhexidine are performed by damaging the cytoplasmic membrane.…”
mentioning
confidence: 99%